Comparison of different zinc stannate structures synthesized at room temperature for photodegradation of dyes and phenol - Khan, Muhammad Najam; Dutta, Joydeep; Thammarat Koottatep; Anal, Anil Kumar; BUITEMS Quetta, Pakistan; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2014)
Nanostructured metal oxides are well known as excellent materials for photocatalysis. Properties of binary semiconducting oxides such as titanium dioxide (TiO2) and zinc oxide (ZnO) are well established. Limitations arise in their performances in new applications and stability under extreme operating conditions. Zinc stannate (ZTO), a ternary semiconducting oxide has shown promise to be useful in applications under extreme conditions such as in acidic environments where ZnO and TiO2 are not suitable. ZTO has shown comparable visible light photocatalytic properties for photodegradation of dyes. Aqueous synthesis of zinc stannate (ZTO) nanoparticles by precipitation at room temperature is studied in this work. Pourbaix diagram was employed to formulate the precipitation reactions and synthesis process. Solution pH was controlled during the synthesis as a major variable. ZTO particles synthesized at room temperature showed good photocatalytic activity under UV light irradiation with degradation rate constant of (k~ 0.0326 min-1). In order to improve visible light photocatalytic activity of ZTO nanoparticles, mixed phase zinc stannate /zinc oxide (ZnO) composites were prepared by co-precipitation at room temperature. Effect of precursor concentrations on the size and morphology of the obtained particles are reported. The composite ZTO/ZnO showed better photodegradation under visible light irradiation compared to ZTO and ZnO nanoparticles with Methylene Blue (MB) as a test chemical contaminant. The degradation rate constant for composite ZTO/ZnO was comparatively higher with 78% MB degraded over a period of one hour illumination (k~ 0.0268 min-1) and ZTO nanoparticles showed 60% degradation (k~ 0.0156 min-1) over the same period. ZnO nanoparticles showed 56% MB degradation (k~ 0.0138 min-1) and control sample containing only MB (10 oM) degraded only 27% (k~ 0.0051 min-1) for the period of one hour illumination Experiments were designed to elaborate on the active species for photocatalytic degradation of the dye. Benzoquinone (BQ) was found to be the most effective scavenger reducing the photodegradation considerably, indicating that O2-{u2022}plays a major role in MB degradation with over 50% increase in photocatalytic activity was observed as compared to photocatalysis in the absence of scavengers. Due to its high stability ZTO and composite ZTO/ZnO are appropriate materials for photodegradation of phenol which is present in large amount in both waste water and ground water. Photocatalytic activity of as synthesized particles was determined using 50 ppm phenol in water as test contaminant. Experiments were carried out in both acidic and basic conditions to assess the stability of the catalyst and role of pH during photocatalysis. Composite material showed enhanced activity at mild acidic conditions. Composite samples show higher photodegradation at initial pH of 6.4 with ~76 % decrease in phenol concentration as compared to ~73 % and ~55 % degradation with ZTO nanoparticles and control samples respectively. Efficiency of photodegradation was observed to be closely related to the isoelectric point of zinc stannate/zinc oxide nanocomposites.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Nanotechnology
Thesis (M. Eng.) - Asian Institute of Technology, 2014
Keywords: Photocatalysis; Semiconductors; Nanostructured materials